Unpacking the 'why' behind strategic emotion expression at work: A narrative review and proposed taxonomy. Issue 5 (October 2020) - Geddes, Deanna; Lindebaum, Dirk
Abstract: Strategic emotion expression constitutes a common-thread phenomenon in emotion regulation and emotion management research across multiple behavioral and social science disciplines. Despite this prevalence, less is known about the "why" behind these observable emotion displays within organizations. Exemplary research is reviewed reflecting the variety of motives behind strategic emotion displays. We argue that significant theoretical opportunity exists with acknowledging motivational differences underlying expressed emotion at work. Our narrative review helps generate a comprehensive and multilevel taxonomy of individual motives (personal and interpersonal), organizational emotion display rules or norms, and socio-cultural emotionologies that reflect dynamic societal expectations and conventions regarding appropriate emotion displays. Strategic emotion expression in organizations reveals the intersection of self- and other-imposed prescriptions and/or restrictions on emotional episodes and distinguishes the nature and purpose of emotive behaviors at work.